Mechanical characterization of auxetic stainless steel thin sheets with reentrant structure - Lekesiz, Hüseyin; Bhullar, Sukhwinder Kaur; Karaca, A. A.; Jun, M. B. G. (Iop Publishing Ltd, 2017)
Smart materials in auxetic form present a great potential for various medical applications due to their unique deformation mechanisms along with durable infrastructure. Both analytical and finite element (FE) models are extensively used in literature to characterize mechanical response of auxetic structures but these structures are mostly thick enough to be considered as bulk material and 3D inherently. Auxetic plates in very thin form, a. e. foil, may bring numerous advantages such as very light design and better biodegradability when needed. However, there is a gap in literature on mechanical characterization of auxetic thin plates. In this study, structural analysis of very thin auxetic plates under uniaxial loading is investigated using both FE method and experimental method. 25 mu m thick stainless steel (316L) plates are fabricated with reentrant texture for three different unit cell dimensions and tested under uniaxial loading using universal testing machine. 25 and 50 mu m thick sheets with same cell dimensions were analyzed using implicit transient FE model including strain hardening and failure behaviors. FE results cover all the deformation schemes seen in actual tests and total deformation level matches with test results. Effect of plate thickness and cell geometry on auxetic behavior is discussed in detail using FE results. Finally, based on FE analysis results, an optimum geometry for prolonged auxetic behavior, high flexibility and high durability is suggested for future potential applications.
Keywords: auxetic materials; thin plates; biomaterials; mechanical behavior; finite element method; transient analysis